CD4+CCR5+ T cells and CCL3+ mast cells are increased in the skin of patients with chronic spontaneous urticaria - Mubariki, Raeda; Samara, Reem; Gimenez-Arnua, Anna Maria; Maurer, Marcus; Bejar, Jacob; Toubi, Elias; Vadasz, Zahava (Frontiers in Immunology, 2024)
Background: The proximity of activated T cells and mast cells in the lesional skin of patients with chronic spontaneous urticaria (CSU) is held to contribute to the development of wheals and angioedema. In a previous study, we demonstrated that increased IL-17 expression in T cells and mast cells in skin lesions of patients with CSU is associated with T/mast cell proximity, but the mechanisms that drive T cell/mast cell co-localization remain unknown. Objectives: To assess if chemokines expressed in lesional CSU skin contribute to T cell/mast cell proximity. Patients and Methods: Biopsies from lesional CSU skin were compared to biopsies from healthy skin for expression of CCR5 and its ligand CCL3 by CD4+ T cells and mast cells respectively. Results: Numbers of CCR5-positive CD4+ T cells in lesional CSU skin were significantly increased as compared to healthy normal skin (p < 0.0001). The number of mast cells expressing CCL3 (ligand for CCR5) in CSU skin was also increased (p < 0.0002) and significant association with T cell close proximity (p < 0.0001) is noticed. Conclusions: The close proximity of T cells and mast cells in the skin of severe CSU may be driven, at least in part by increased CCR5 and CCL3 expression. Therapies that target CCL3 interaction with CCR5 should be assessed for their effects in CSU